KUALITAS SPERMATOZOA DAN INDEKS FERTILITAS TIKUS PUTIH DEWASA (Rattus novergicus L.) SETELAH PEMBERIAN EKSTRAK DAUN WUNGU (Graptophyllum pictum. L.Grifft) - Hendro Pranoto (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2018)
This research objective is to identify the effects of wungu leaf extract (Graptophyllum pictum L. Griff) on the fertility index and spermatozoa of normal morphology in male rat ( Rattus novergicus.L). Fifteen male and 45 female rats of 9 to 10 weeks old were used as research samples. The fifteen male rats were divided into five treatment groups of wungu extract dosage: control I (0mg/KgBW), control II (0.5ml olive oil), dosage 1 (100mg/KgBW), dosage 2 (200mg/KgBW), and dosage 3 (400mg/KgBW) for 60 days. The extract was given orally and each group consisted of three test rats as repetition. On the day 55 to day 60, each test male animal was mated with three female rats. After 60 days, an observation was done to 15 male and 45 female rats to identify fertility index. Normal spermatozoa morphological observation with microscope. The data obtained were tested by Analysis of Variance Test (ANOVA ? = 0.05) and Duncan’s Multiple Range Test (DMRT). Based on the observation and statistical analysis, it was found that wungu leaf extract of different dosages did not give significant effects on fertility index but have significant effects on spermatozoa of normal morphology. This was proven by the fact that the higher the dosage given, the worse the spermatozoa of normal morphology. Based on Linear Regression Analysis, it was found significant correlation between dosage variation extract of wungu leaf and fertility index, and number of normal spermatozoa.